Pathogenic KIAA0586/TALPID3 variants are associated with defects in primary and motile cilia - Jacqueline E. Taudien; Diana Bracht; Heike Olbrich; Sebastian Swirski; Fulvio D’Abrusco; Bert Van der Zwaag; Maike Möller; Thomas Lücke; Norbert Teig; Ulrika Lindberg; Kai Wohlgemuth; Julia Wallmeier; et al. (iScience)
Summary: Pathogenic variants in KIAA0586/TALPID3 are associated with the ciliopathy Joubert syndrome (JS). We report individuals with KIAA0586/TALPID3 variants affected by primary and motile cilia defects leading to JS and chronic destructive airway disease. DNA variants were detected in three families by sequencing. In two unrelated families, a deep-intronic variant (KIAA0586/TALPID3:c.3990 + 3186G>A) activated a cryptic exon. We performed histological and functional analyses in native and air-liquid interface (ALI) cultured respiratory cells. Primary cilia lengths were measured in patient-derived fibroblasts. Our data associate KIAA0586/TALPID3 variants with a syndrome combining JS and chronic destructive airway disease, reduced number of motile cilia, disorganized basal body location, and ciliary clearance malfunction. Additionally, patient-derived cell lines showed primary cilia defects. Disease causing KIAA0586/TALPID3 variants, including a deep-intronic sequence variant, were associated with primary and motile cilia defects in JS patients. The combination of JS and respiratory symptoms should be considered indicative for KIAA0586/TALPID3 sequence alterations.